Biodegradation of organic content via activated sludge seeding coupled with aeration in simulated self-purification sewer system - Kh. Al-Jumaili, Kareem; H. Al-Anbari, Riyadh; A. Al-khateeb, Tala (Iraqi Journal of Civil Engineering, 2018)
Partial degradation of organic materials presented in sewage water had been conducted in the current research in a simulated sewer system. The process had been improved by aeration and seeding with activated sludge to reveal the effect of increasing the amount of biomass in the system. Three ambient temperatures were conducted as 10, 20, and 30 OC to display the influence of temperature on the degradation process. The results revealed that adding activated sludge to the system in a ratio of 50/50 (v/v) had a significant influence on the degradation as more microorganisms required more organic nutrients. In the other hand, increasing the operating temperature indicated positive influence in terms of soluble chemical oxygen demand (SCOD) removal as temperature motivated the living biomass towards severe degradation.